Sistema informático de gestión de ventas y servicios técnicos en la empresa s-compu del cantón Pedernales - Pinargote Pincay, Miguel Ángel (2014)
The company S-Compu from Pedernales was developed a control system to optimize sales records and technical services the programming language used to develop the software was Visual Basic 2010, using the integrated development environment of Microsoft Visual Studio version. NET and in conjunction with programing oriented to object, as manager database programming SQL Server 2008R2 was used whose main function is to store and retrieve data as requested by software applications. Prototyping methodology was used for fast development System, together with the inductive -deductive methods, including the same techniques that allowed collecting information, to identify needs and find solutions. After the implementation of the system, time quiz demonstrated the optimization the sales processes and technical services by 76%, allowing greater ease when executing business processes of the organization.